2014
DOI: 10.1186/1471-2350-15-42
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in DDR2 causing spondylo-meta-epiphyseal dysplasia with short limbs and abnormal calcifications (SMED-SL) results in defective intra-cellular trafficking

Abstract: BackgroundThe rare autosomal genetic disorder, Spondylo-meta-epiphyseal dysplasia with short limbs and abnormal calcifications (SMED-SL), is reported to be caused by missense or splice site mutations in the human discoidin domain receptor 2 (DDR2) gene. Previously our group has established that trafficking defects and loss of ligand binding are the underlying cellular mechanisms of several SMED-SL causing mutations. Here we report the clinical characteristics of two siblings of consanguineous marriage with sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 46 publications
(63 reference statements)
0
27
0
Order By: Relevance
“…First, human DDR2 mutations cause spondylometa-epiphyseal dysplasia (SMED), a skeletal disorder associated with dwarfism, short fingers, bowing of long bones, abnormal calcifications, and craniofacial abnormalities. (10,11) In addition, polymorphisms in DDR2 are associated with low bone mineral density (BMD) and fracture risk in a Han Chinese population. (12) Mice harboring deletions in the Ddr2 locus have a SMED-like phenotype characterized by dwarfism and reduction in total BMD.…”
Section: Introductionmentioning
confidence: 99%
“…First, human DDR2 mutations cause spondylometa-epiphyseal dysplasia (SMED), a skeletal disorder associated with dwarfism, short fingers, bowing of long bones, abnormal calcifications, and craniofacial abnormalities. (10,11) In addition, polymorphisms in DDR2 are associated with low bone mineral density (BMD) and fracture risk in a Han Chinese population. (12) Mice harboring deletions in the Ddr2 locus have a SMED-like phenotype characterized by dwarfism and reduction in total BMD.…”
Section: Introductionmentioning
confidence: 99%
“…Only seven mutations have been revealed in DDR2 , four missense, two deletions, and one splice‐site mutations. These mutations lead to loss‐of‐function by at least two different mechanisms, namely, defects in DDR2 targeting the plasma membrane and its ligand‐binding activity [Bargal et al, ; Ali et al, ; Al‐Kindi et al, ] (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of function of human or mouse Ddr2 gene leads to dysplasia in bones [20,21,22,23]. Therefore, the regulation of DDR2 in osteoblast differentiation is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Ddr2 knockout mice and slie mice (mouse colony with spontaneous autosomal-recessive mutation in the Ddr2 locus) exhibit short long bones and irregular growth of flat bones [20]. Human Ddr2 gene mutation causes a rare form of dwarfism, spondylo-meta-epiphyseal dysplasia short limb-hand type (SMED-SL) [21,22,23]. Our and other's studies also demonstrated that DDR2 plays essential roles in osteoblast differentiation and chondrocyte maturation by modulating the phosphorylation and transactivity of Runx2 in an ERK MAPK-dependent manner [24,25].…”
Section: Introductionmentioning
confidence: 99%